Rethinking urban land grabbing: a decolonial political ecology perspective to reveal a pluriverse of alternatives - Aldrete Flores Daran, Luisa (2025)
This thesis employs a decolonial political ecology approach to rethink the contemporary urban land-grabbing conflict on the periphery of a medium-sized city in Mexico, highlighting the defence of communal territories as evidence of the pluriverse. Drawing on the epistemological decision of what Mignolo's defines as ‘dwelling in the border’— where alternatives are possible— this thesis uses a personal reflexive process as a decolonial tool to illuminate other worlds and their territorial struggles. These struggles involve resisting, assimilating, and reproducing the modern world system amidst urban expansion while defending other ways of being, doing and thinking. By focusing on the decolonial struggle over territory, this thesis fosters an epistemological and transversal dialogue among the different but interconnected worlds entangled in the urban land-grabbing conflict. It creates a space for co-producing knowledge and exploring alternative pathways for plural and ethical futures in this and other similar contexts, suggesting a new direction for research in this field.